Population Structure of the Eastern Prawn, Macrobrachium nipponense (Crustacea, Decapoda, Palaemonidae), in the First Years of its Introduction into the Kiliya Delta of the Danube - K. Ye. Zorina-Sakharova; K. I. Hoshka; A. V. Lіashenko; V. A. Lіashenko (Zoodiversity)
The population structure, growth, and relative condition factor of the eastern prawn, Macrobrachium nipponense (De Haan, 1849), in the first years of its introduction into the Kiliya Delta of the Danube were studied. The quantitative predominance of males over females (♀ : ♂ = 1.0 : 2.5) was established, with egg-bearing females comprising 10.0 % of the total prawn population. PCA results indicate that TL and AL are the primary differences separating females from most males, while egg-bearing and non-egg-bearing females differ in most morphometric parameters, with the key traits being RChL, LChL, and 1AbH. LDA results showed that males, egg-bearing and non-egg-bearing females differed significantly in the population based on the studied characteristics. The growth coefficients indicated a positive allometric growth type for males (b = 3.62) and near-isometric growth for females (b = 3.09). For 65.4 of females and 57.8 % of males, the values of the condition factor Kn > 1, indicating high fatness in individuals of both sexes.